VIEW FROM HERE – ENGLISH IN INDIA: THE RISE OF DALIT AND NE LITERATURE (International Journal of Food and Nutritional Sciences, 2021)
This article argues that transactionsbetween the English text and localconditions are an important aspect ofdevelopments in English in Indiadetermining interpretations in teaching andresearch.